The colour of environmental fluctuations associated with terrestrial animal population dynamics - David Gilljam (Global Ecology and Biogeography, 2018)
AIM:The temporal structure (colour) of environmental variation influences population fluctuations, extinction risk and community stability. However, it is unclear whether environmental covariates linked to population fluctuations are distinguishable from a purely random process (white noise). We aim to estimate colour coefficients and relative support for three models commonly representing coloured stochastic processes, in environmental series linked to terrestrial animal population fluctuations. LOCATION:North-America and Eurasia.TIME PERIOD:1901-2002MAJOR TAXA STUDIED:Birds, insects and mammals.METHODS:We analysed multiple abiotic environmental covariates, comparing point estimates and confidence intervals of temporal structure in competing models fitted using white noise, autoregressive (AR[1]) and 1/f processes in the time-domain and frequency-domain (where time-series were analysed following decomposition into different sinusoidal frequencies and their relative powers). All animal time-series were sampled annually for ≤ 50 years, potentially inflating Type-II errors. We also considered 101-year series of matched environmental covariates, performing a statistical power analysis evaluating our ability to draw robust conclusions.RESULTS:Temperature-related variables were associated with the largest fraction of population fluctuations. 93% of shorter environmental series were indistinguishable from white noise, limited by time-series length and associated with wide confidence intervals. The longer environmental series analysed in the time-domain offered sufficiently high statistical power to correctly identify colour estimates ≥ |0.27|, indicating 20% of series were best described by a slightly reddened noise process.MAIN CONCLUSIONS:Focusing on the short time-scales typically available for ecologists, most environmental variables associated with terrestrial animal population fluctuations are best characterised by white noise processes, although Type-II errors are common. Correctly detecting intermediately coloured noise with power 0.8 requires at least 16 data points in the time or 47 points in the frequency-domain. Over longer time-scales, where Type-II errors are less likely, one-fifth of populations are associated with coloured (often reddened) variables.